NON-PLACES OF MEMORY: SPACE, MATERIALITY AND FALSE CEMETERIES - POSŁUSZNY, Łukasz (Studia Universitatis Babes-Bolyai Studia Europaea, 2020)
The article deals with the concept of non-place of memory (NPM). Author defines NPM broadly as entity which once created by people lost its perceptive properties as man-made, but at the same time kept it material basis. In the narrower sense of the definition NPM are places of murder and bodies deposition sites which are either unrecognized as such or haven’t been yet changed into places of memory. The analysis is based mostly on cases of Roma massacres in Poland which took place during II World War and compared with the history of burials and concept of cemetery. Transitions of NMP is then explained by using the Mary Douglas’ concept of anomaly.